Preparation of Ag/Ga2O3 nanofibers via electrospinning and enhanced photocatalytic hydrogen evolution. (3rd August 2017) - Han, Chunqiu; Mao, Wutao; Bao, Keyan; Xie, Haiquan; Jia, Zhuoya; Ye, Liqun
Abstract: In this paper, gallium oxide (Ga2 O3 ) was modified by in situ silver (Ag) to improve the photocatalytic activity for hydrogen (H2 ) evolution. The photocatalysts Ga2 O3 and Ag/Ga2 O3 were synthesized via electrospinning and calcination, and characterized by X-ray diffraction patterns (XRD), Brunauer-Emmett-Teller (BET), scanning electron microscope (SEM), transmission electron microscopy (TEM), UV–vis diffuse reflectance spectra (DRS) and X-ray photoelectron spectroscopy (XPS). It is observed that the 1% Ag/Ga2 O3 had higher activity than that of the pure Ga2 O3 for photocatalytic H2 evolution. Photoluminescence spectra (PL) and transient photocurrent analysis indicated that the high separation efficiency of photo-generated carriers of Ag/Ga2 O3 resulted in the high photocatalytic H2 evolution. Graphical abstract: Ag/Ga2 O3 nanofibers photocatalysts were synthesized via electrospinning and showed higher activity than pure Ga2 O3 for photocatalytic H2 evolution. Highlights: Ga2 O3 and Ag/Ga2 O3 nanofibers photocatalysts were synthesized via electrospinning. 1% Ag/Ga2 O3 had higher activity than pure Ga2 O3 for photocatalytic H2 evolution. Ag nanoparticle improved the separation efficiency of photo-generated carriers.